DD-07 INCISIONAL HERNIA FOLLOWING LAPAROSCOPIC COLORECTAL LIVER METASTASIS RESECTION. FIRST COMPARATIVE STUDY. (13th October 2022) - Hassan, A; Elfarouq, A; Katheria, V; Subar, D
Abstract: Aim: Since first laparoscopic liver surgery (LLR) in 1991, no literature to compare Incisional hernia (IH) incidence between LLR and open Resection (OLR). This is the first comparative study Material and methods: Single centre retrospective review of Colorectal Liver Metastasis resections between 2011 till 2018. The primary end point is developing IH related to liver resection. Incidence of IH was compared between LLR and OLR. Factors including Age, Gender, Diabetes Mellitus, Steroid intake, Pre-op Creatinine and Albumin, Previous Liver resection ASA score were compared between both groups. Subcutaneous and peri-renal fat thickness measured as indicative of fat distribution. Numeric results presented in Mean±SD. SPSS 20 (IBM, Armonk, USA) used for statistical analysis. p ≤ 0.05 was considered statistically significant Results: 247 procedures with follow-up 41 ± 29 Months. IH was observed in 48 case (19.4%). Incidence was 10%, 19% at 1, 3 years respectively (Kaplan-Meier). 87 case (35%) had LLR and 160 (65%) OLR. OLR had lower pre-op Albumin (32±9 Vs 35±8 g/L, p 0.01, Mann-Whitney U), longer hospital stay (10±7 Vs 6±4 days, p 0.00, Mann-Whitney U) and more major liver resections i.e. Resection of 3 or more segments (58% Vs 29% in LLR, p 0.00, Chi 2) . No difference in IH Incidence in LLR (8%, 19% Vs 10%, 19%) and OLR at 1, 3 years respectively. Similarly, no difference in hernia size (53±37 mm in LLR Vs 50 ± 33 in OLR, p 0.96, Mann-Whitney U) Conclusion: No difference in IH incidence or size between LLR and OLR.